A qualitative exploration of priorities for quality improvement amongst Aboriginal and Torres Strait Islander primary health care services - Karen Carlisle; Veronica Matthews (Quandamooka); Michelle Redman-MacLaren; Kristina Vine; Nalita Nungarrayi Turner (Anmatyerre/Jaru); Catrina Felton-Busch (Yangkaal/Gangalidda); Judy Taylor; Sandra Thompson; Donald Whaleboat (Meriam Le); Sarah Larkins; With the LEAP Learning Community (BMC, 2021)
Abstract Background Achieving quality improvement in primary care is a challenge worldwide, with substantial gaps between best practice and actual practice. Within the context of Australia, Aboriginal and Torres Strait Primary Health Care (PHC) services have great variation across settings, structures and context. Research has highlighted how these contextual differences can critically influence the success of Quality Improvement (QI) interventions and outcomes. Less understood is the interaction between local context and other factors, which may impact the implementation of QI interventions. This paper aims to explore the strengths and challenges in QI for Aboriginal and Torres Strait Islander PHC services and their priorities for improvement. Methods A multiple case study design was adopted, working with eight Aboriginal and Torres Strait Islander PHC services in Northern Territory, Queensland and Western Australia. Data were collected via a health service survey, semi-structured interviews with health service staff and service users and researcher observations, to explore QI and perceptions of care quality at the service level. Data reported here were analysed using an iterative thematic technique, within-case and across-case. Results A total of 135 interviews were conducted with health service staff, service users and community members. Participants emphasised the centrality of resilient community, committed workforce and valued Aboriginal and Torres Strait Islander team members in delivering care. A shared purpose around improving the health of community was a significant driver. Key challenges included staff turnover and shortages, a complex and overwhelming acute and chronic care workload, building relationships and trust between health services and the community. Service-suggested priority areas for improvement were categorised into five themes: i) cultural safety (community driving health and planning for culturally safe services); ii) community engagement (through clinical activities in the community); iii) shared ownership and a team approach around QI; iv) strengthening systems and consistent ways of doing things in the health service; and v) strengthening local workforce (and resources for a culturally safe workforce). Conclusions These findings advance understandings of relational, community and cultural factors which are identified priorities for the delivery of quality care in Aboriginal and Torres Strait Islander PHC services across varied contexts.